2021
DOI: 10.1186/s12862-021-01936-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and selective grain make plasticity 'take the lead' in adaptive evolution

Abstract: Background Biological evolution exhibits an extraordinary capability to adapt organisms to their environments. The explanation for this often takes for granted that random genetic variation produces at least some beneficial phenotypic variation in which natural selection can act. Such genetic evolvability could itself be a product of evolution, but it is widely acknowledged that the immediate selective gains of evolvability are small on short timescales. So how do biological systems come to exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 50 publications
3
27
0
Order By: Relevance
“…Such mechanistic, development‐based models can provide a causal understanding of the phenotypic consequences of changes in environmental variables, making it possible to construct an Environment‐Phenotype (EP) ‘map’ [Box‐2]. [ 1,33,39,60,61 ] Consider, for instance, the effect of temperature on the number and size of scutes in the turtle carapace. [ 62,63 ] Temperature typically increases cell division, suggesting that increases in temperature might lead to larger carapaces containing an increasing number of scutes.…”
Section: The Environment‐phenotype Mapmentioning
confidence: 99%
See 2 more Smart Citations
“…Such mechanistic, development‐based models can provide a causal understanding of the phenotypic consequences of changes in environmental variables, making it possible to construct an Environment‐Phenotype (EP) ‘map’ [Box‐2]. [ 1,33,39,60,61 ] Consider, for instance, the effect of temperature on the number and size of scutes in the turtle carapace. [ 62,63 ] Temperature typically increases cell division, suggesting that increases in temperature might lead to larger carapaces containing an increasing number of scutes.…”
Section: The Environment‐phenotype Mapmentioning
confidence: 99%
“…Furthermore, each type of generative input is represented as an independent (i.e., orthogonal) axis whose values can be modified without affecting the others. Such an independence means that each type of input is irreducible to one another [ 61 ] , and that their values can be (at least theoretically) combined in many ways (i.e., {G 1 ,E 1 ,D 1 }, {G 1 ,E 1 ,D 2 }, … {G n ,E n ,D n }). The 3P‐map makes it easy to grasp why phenotypes and their variation depend on genes, environmental and epigenetic factors.…”
Section: Putting the Maps Together Helps To Characterize The Roles Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, it 57 has been widely used to investigate how their structural and 58 functional properties change after evolution in static 20,22,23 59 or fluctuating 18,[24][25][26] environments. Only a few studies have 60 considered phenotypic plasticity by incorporating sensors into 61 the network [27][28][29][30] . These studies showed that the evolution 62 of phenotypic plasticity generates a correlation of phenotypic 63 variation between traits 27,29 and affects the amount of pheno-64 typic variation observed among populations encountering novel D R A F T changes (without changing genotype).…”
Section: On the Origin Of Phenotypic Plasticitymentioning
confidence: 99%
“…Only a few studies have 60 considered phenotypic plasticity by incorporating sensors into 61 the network [27][28][29][30] . These studies showed that the evolution 62 of phenotypic plasticity generates a correlation of phenotypic 63 variation between traits 27,29 and affects the amount of pheno-64 typic variation observed among populations encountering novel D R A F T changes (without changing genotype). In the following section, 87 we explain how a sensor gene is incorporated in the model of 88 Watson et al 18 and the other modifications we perform.…”
Section: On the Origin Of Phenotypic Plasticitymentioning
confidence: 99%